POTENTIAL DISTRIBUTION OF HUMAN CYTOMEGALOVIRUS IN AL-FURAT AL-AWSET AREA of Iraq - Al-muhanna, Abbas Shakir Jwad; Al- muhanna, Enass Kareem (Al-Qadisiyah Journal of Pure Science, 2017)
A total of 522 patients suffering from abortion or another genital tract problem were studied to determinate the role of cytomegalovirus in causing abortion in women suffering from frequent abortion, dependent on increasing the level of IgG and IgM antibodies in serum of patient.274 (52.4%) gave positive results, versus 248 (44.6%) gave negative results. (26%) in Karbala governorate (13%) in Al-Najaf, and (13.4%) in Al-Diwanyia. Human cytomegalovirus was detected in 261 (93.3%) of female versus 13(6.7%) in male. The highest number of CMV infection was appear in age between (25-30, 20-25 and 20-25) accounted 38 (7.3%) in Karbala, 23 (4.4%) in AL-Najaf governorate and 19(3,6%) in AL-Diwanyia respectively